β-Cyclodextrin Inclusion Complexes of Cinnamomum camphora Essential Oil: A Comparative Study on Encapsulation Strategies, Physicochemical Stability, and Cytotoxic Profile - Constandil-Cordova, L; Juica, N (Multidisciplinary Digital Publishing Institute (MDPI), 2026)
Background/Objectives: Essential oils (EOs) from plants of the genus Cinnamomum have been widely used based on their antimicrobial, antioxidant, and anti-inflammatory properties. However, their elevated volatility and limited aqueous solubility restrict their use in pharmaceutical and food formulations. Cyclodextrins (CDs) have emerged as a promising strategy to overcome these limitations through the formation of inclusion complexes. Methods: In this study, inclusion complexes of essential oil from C. camphora L. (EOCNM) with beta-cyclodextrin (beta-CD) were developed using physical mixing (PM), ultrasonic treatment (US), and freeze-drying (FD). The inclusion complexes were physicochemically characterized by differential scanning calorimetry (DSC), thermogravimetric analysis (TG/DTG), X-ray diffraction (XRD), and scanning electron microscopy (SEM) to evaluate their physicochemical interactions and complexation efficiency. Results: Our results demonstrated successful complex formation, with the FD and US methods showing greater amorphization and stronger inclusion characteristics compared to the PM method. Thermal analysis confirmed improved physicochemical stability of the essential oil when complexed with beta-CD. Furthermore, the cytotoxicity assay of the complexes was assessed using the MTT assay and J774 macrophage cells. The complexes exhibited low cytotoxicity, indicating their potential biocompatibility for biomedical and food applications. Conclusions: Overall, beta-CD encapsulation effectively enhanced the physicochemical stability and safety profile of C. camphora essential oil, providing a promising strategy for its controlled delivery and protection against degradation.